Exploiting the Metabolic Consequences of PTEN Loss and Akt/Hexokinase 2 Hyperactivation in Prostate Cancer: A New Role for δ-Tocotrienol - Fabrizio Fontana (International Journal of Molecular Sciences, 2022)
The Warburg effect is commonly recognized as a hallmark of nearly all tumors. In prostate cancer (PCa), it has been shown to be driven by PTEN loss- and Akt hyperactivation-associated upregulation of hexokinase 2 (HK2). δ-Tocotrienol (δ-TT) is an extensively studied antitumor compound; however, its role in affecting PCa glycolysis is still unclear. Herein, we demonstrated that δ-TT inhibits glucose uptake and lactate production in PTEN-deficient LNCaP and PC3 PCa cells, by specifically decreasing HK2 expression. Notably, this was accompanied by the inhibition of the Akt pathway. Moreover, the nutraceutical could synergize with the well-known hypoglycemic agent metformin in inducing PCa cell death, highlighting the crucial role of the above metabolic phenotype in δ-TT-mediated cytotoxicity. Collectively, these results unravel novel inhibitory effects of δ-TT on glycolytic reprogramming in PCa, thus providing new perspectives into the mechanisms of its antitumor activity and into its use in combination therapy.